Examining the Nuna-Rodinia supercontinent cycle in East Antarctica and testing correlations to the southwest United States: evidence from the Read Group (Shackleton Range) and the Nimrod Complex - Joe H. Metcalfe; Teal R. Riley; Michael J. Flowerdew; Nicholas J. Gardiner; Sebastian Fischer; Ian L. Millar; Joshua M. Garber; Maurice Brodbeck; David van Acken; Cristina Talavera; Heejin Jeon; Martin J. Whitehouse (Precambrian Research, 2026)

Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

Introducing the maximum displacement technique for structural enhancement of rectangular and curved plates in thermoset 3D-printed concrete formwork - Zuffain Hussan; Marco Brander; Berin Šeta; Jon Spangenberg; Sebastian Andersen; Gregor Fischer (Engineering Structures, 2026)

The health, environmental, and economic dimensions of future dietary transitions in Argentina - Ezequiel M. Arrieta; Carlos González Fischer; Sebastian Aguiar; Milva Geri; Roberto J. Fernández; Julia Becaria Coquet; Carlos M. Scavuzzo; Andres Rieznik; Alberto León; Alejandro D. González; Esteban G. Jobbágy (Sustainability Science, 2026)

New Research Perspectives in Light of Dense Cross-Border Experiments in West Bohemia and Vogtland Regions - Pınar Büyükakpınar; Torsten Dahm; Marius Isken; Jana Doubravová; Dana Křížová; Marcel van Laaten; Josef Vlček; Catherine Alexandrakis-Zieger; Sofia-Katerina Kufner; Jakub Klicpera; Heiko Woith; Jan Mrlina; et al. (Studia Geophysica et Geodaetica, 2026)
The Eger Large-N International Seismic Experiment (ELISE) is a major cross-border project deploying a temporary network of over 300 broadband and short-period seismic stations in the West Bohemia/Vogtland region, located at the border of Czechia and Germany. This experiment offers new research opportunities in one of the most seismically and geodynamically active intraplate regions in Europe, characterized by recurrent earthquake swarms resulting from magmatic crustal fluids and mantle CO₂ degassing processes. The collision and thrusting of Variscan tectonic domains have created a unique natural laboratory to investigate how ancient structures influence present-day magmatic processes and fluid–rock interactions. ELISE aims to address fundamental questions regarding the origin of swarms, their dynamics, and hazard potential, as well as their relationship with geodynamic activities in the region. The stations of this dense array have been operating since August 2025 and will record for up to 18 months. They will enable high-resolution imaging of crustal structures through the use of high-resolution earthquake locations, ambient noise tomography, receiver function analyses, and local earthquake tomography. Based on previous experience, we hypothesize that intensifying seismic networks will reveal at least ten times more local earthquakes, ultimately clarifying the mechanisms of swarm earthquakes by constraining fluid migration paths and structural and geological boundary conditions. Better earthquake locations, together with high-resolution subsurface models of different quantities, will provide new insights into the interaction between tectonic and fluid-induced seismicity revealing the possible role of carbonate brines and melts in the formation of swarms. This will improve our understanding of geodynamic and fluid-magma interactions in intraplate tectonic settings. This paper provides an overview of the ongoing ELISE experiment. It outlines its goals, scientific framework, and expected contributions.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Results of the SSM-SICOPS melt tests of the EU-SAFEST project - Gert Langrock; Torsten Keim; Manfred Fischer; Matthias Braun; Sebastian Kohn; Roland Hofmann; Rainer Bezold; Martin Neumeister; Sevostian Bechta; Patrick Isaksson (Annals of Nuclear Energy, 2025)

How to build (in) the future? Legitimacy of socio-technical visions in a bio-based construction sector - Lennart Fischer; Sebastian Losacker (Environmental Innovation and Societal Transitions, 2025)

Strategic solar module stockpiling in the EU: A scenario-based analysis of costs and benefits beyond 2030 - Sebastian Zwickl-Bernhard; Maximilian Oitzinger; Helen Anais Fischer; Stian Backe (Energy Policy, 2025)

Correction: Modeling lactate threshold in cycling—influence of sex, maximal oxygen uptake, and cost of cycling in young athletes - Jonas Fischer; Finn Hävecker; Sanghyeon Ji; Patrick Wahl; Sebastian Keller (European Journal of Applied Physiology, 2025)

Modeling lactate threshold in cycling—influence of sex, maximal oxygen uptake, and cost of cycling in young athletes - Jonas Fischer; Finn Hävecker; Sanghyeon Ji; Patrick Wahl; Sebastian Keller (European Journal of Applied Physiology, 2025)
Purpose Understanding physiological determinants of lactate threshold 2 (LT2) is crucial for tracking adaptations and deriving individualized training recommendations in cycling. Therefore, the study investigated: 1. the accuracy of modeling power output at LT2 in young athletes of both sexes using maximal oxygen uptake ( $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak ), fractional utilization of $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak (% $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak ), and oxygen cost of cycling (Cc); 2. the influence of Cc determination on the model accuracy; 3. the influence of the model predictors and inclusion of maximal lactate accumulation rate ( $${\dot{c}}La_max$$ c ˙ L a max ) on power at LT2 depending on sex. Methods Eighty-three cyclists and triathletes (22 females, 61 males; age [median and IQR]: 14.6 [13.8–17.6] years, $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak [mean ± SD]: 59.2 ± 6.5 mL⋅kg –1 ⋅min –1 ) performed an incremental test to determine power at LT2, $${\dot{V}}O_{2_peak},$$ V ˙ O 2 peak , % $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak at LT2, and Cc (assessed at 3 W⋅kg –1 , 75% $${\dot{V}}O_{2_peak},$$ V ˙ O 2 peak , and 90% LT2). Results Modeled and experimentally determined power at LT2 demonstrated excellent agreement for all, male and female athletes (ICC $$\ge$$ ≥ 0.961), with Cc at 90% LT2 providing the highest accuracy (ICC $$\ge$$ ≥ 0.986). The three physiological determinants explained $$\ge$$ ≥ 98% of the variance in power at LT2, with the largest unique contribution from $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak (62 and 67% of total $$R^2$$ R 2 ), followed by Cc (8 and 34%) and % $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak at LT2 (5 and 12%) in males and females, respectively, while $${\dot{c}}La_max$$ c ˙ L a max did not improve the regression. Conclusion $${\dot{V}}O_{2_peak}, $$ V ˙ O 2 peak , % $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak at LT2 and Cc accurately predict power at LT2 in young cycling athletes independent of sex, with determination of Cc at 90% LT2 providing the highest accuracy. While $${\dot{V}}O_{2_peak}$$ V ˙ O 2 peak contributes most to LT2 in both sexes, Cc appears more important in young females.

The EnMAP spaceborne imaging spectroscopy mission: Initial scientific results two years after launch - Sabine Chabrillat; Saskia Foerster; Karl Segl; Alison Beamish; Maximilian Brell; Saeid Asadzadeh; Robert Milewski; Kathrin J. Ward; Arlena Brosinsky; Katrin Koch; Daniel Scheffler; Stephane Guillaso; et al. (Remote Sensing of Environment, 2024)

One to rule them all? Assessing the performance of sustainable forest management indicators against multitaxonomic data for biodiversity conservation - Yoan Paillet; Livia Zapponi; Peter Schall; Jean-Matthieu Monnet; Christian Ammer; Lorenzo Balducci; Steffen Boch; Gediminas Brazaitis; Alessandro Campanaro; Francesco Chianucci; Inken Doerfler; Markus Fischer; et al. (Biological Conservation, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Loss-of-function variants affecting the STAGA complex component SUPT7L cause a developmental disorder with generalized lipodystrophy - Johannes Kopp; Leonard A. Koch; Hristiana Lyubenova; Oliver Küchler; Manuel Holtgrewe; Andranik Ivanov; Christele Dubourg; Erika Launay; Sebastian Brachs; Stefan Mundlos; Nadja Ehmke; Dominik Seelow; et al. (Human Genetics, 2024)
Generalized lipodystrophy is a feature of various hereditary disorders, often leading to a progeroid appearance. In the present study we identified a missense and a frameshift variant in a compound heterozygous state in SUPT7L in a boy with intrauterine growth retardation, generalized lipodystrophy, and additional progeroid features. SUPT7L encodes a component of the transcriptional coactivator complex STAGA. By transcriptome sequencing, we showed the predicted missense variant to cause aberrant splicing, leading to exon truncation and thereby to a complete absence of SUPT7L in dermal fibroblasts. In addition, we found altered expression of genes encoding DNA repair pathway components. This pathway was further investigated and an increased rate of DNA damage was detected in proband-derived fibroblasts and genome-edited HeLa cells. Finally, we performed transient overexpression of wildtype SUPT7L in both cellular systems, which normalizes the number of DNA damage events. Our findings suggest SUPT7L as a novel disease gene and underline the link between genome instability and progeroid phenotypes.

Silicon isotopes in an Archaean migmatite confirm seawater silicification of TTG sources - Madeleine E. Murphy; Jane E. Macdonald; Sebastian Fischer; Nicholas J. Gardiner; Richard W. White; Paul S. Savage (Geochimica et Cosmochimica Acta, 2024)

NIKE-MED – Nachhaltige Interdisziplinarität in Komplexen Einsätzen unter Tage – MEDical Treatment - Robert Galler; Robert Wenighofer; Markus Karlseder; Benjamin Roszipal; Sebastian Egger-Lampl; Michael Lindenthal; Barbara Juen; Dietmar Kratzer; Peter Hofer; Thomas Wegscheider; Philip Fischer; Julian Eder; et al. (BHM Berg- und Hüttenmännische Monatshefte, 2023)
Zusammenfassung Das Projekt NIKE-MED zielt darauf ab, die Effizienz und Effektivität der Einsatzkräfte bei der Bewältigung von Notfällen insbesondere bei Großschadensereignissen zu erhöhen, um die Sicherheit der betroffenen Personen zu gewährleisten. Komplexe Einsätze unter Tage sind mit einem Massenanfall von Opfern mit sehr spezifischen Verletzungsmustern, die man aus bewaffneten Konflikten kennt (Vergiftungen, Verbrennungen, Schuss- und Splitterverletzungen, Verletzungen durch großflächige mechanische Gewalteinwirkung) sowie besonderen Herausforderungen (Kontamination, Dynamiken großer Menschenmengen) verbunden. Basierend auf einem Referenzszenario, in welchem vergangene Ereignisse zu einer hochkomplexen untertägigen Lage verdichtet wurden, konnten Abläufe evaluiert und eine Applikation für die Einsatzkräfte zur Optimierung der notfallmedizinischen Versorgung entwickelt werden. In weiterer Folge wird es nötig sein, Erfordernisse für die Entwicklung strategischer Reservekapazitäten abzuleiten, um für derartige Fälle gerüstet zu sein.

The EnMAP imaging spectroscopy mission towards operations - Tobias Storch; Hans-Peter Honold; Sabine Chabrillat; Martin Habermeyer; Paul Tucker; Maximilian Brell; Andreas Ohndorf; Katrin Wirth; Matthias Betz; Michael Kuchler; Helmut Mühle; Emiliano Carmona; et al. (Remote Sensing of Environment, 2023)

EEG-based sensory testing reveals altered nociceptive processing in elite endurance athletes - Malte Anders; Elias Dreismickenbecker; Johannes Fleckenstein; Carmen Walter; Elena K. Enax-Krumova; Michael J. M. Fischer; Matthias Kreuzer; Sebastian Zinn (Experimental Brain Research, 2023)
Increased exercise loads, as observed in elite athletes, seem to modulate the subjective pain perception in healthy subjects. The combination of electroencephalography (EEG) and standardized noxious stimulation can contribute to an objective assessment of the somatosensory stimulus processing. We assessed the subjective pain ratings and the electroencephalogram (EEG)-based response after standardized noxious mechanical and thermal stimuli as well as during conditioned pain modulation (CPM) in 26 elite endurance athletes and compared them to 26 recreationally active controls. Elite endurance athletes had consistently stronger somatosensory responses in the EEG to both mechanical and thermal noxious stimuli than the control group. We observed no significant group differences in the subjective pain ratings, which may have been influenced by our statistics and choice of stimuli. The CPM testing revealed that our conditioning stimulus modulated the subjective pain perception only in the control group, whereas the EEG indicated a modulatory effect of the conditioning stimulus on the spectral response only in the athletes group. We conclude that a higher activation in the cortical regions that process nociceptive information may either be an indicator for central sensitization or an altered stimulus salience in the elite endurance athletes’ group. Our findings from our CPM testing were limited by our methodology. Further longitudinal studies are needed to examine if exercise-induced changes in the somatosensory system might have a critical impact on the long-term health of athletes.

Biochar-Fertilizer Blends—a Valuable Soil Amendment for Asparagus Cultivation? - Sebastian Meyer; Daniel Fischer; Anne Meyer; Erik Karltun; Malin Pettersson Silvén (Journal of Soil Science and Plant Nutrition, 2022)

Galectin network in osteoarthritis: galectin-4 programs a pathogenic signature of gene and effector expression in human chondrocytes in vitro - Katharina M. Pichler; Anita Fischer; Jürgen Alphonsus; Catharina Chiari; Sebastian Schmidt; Michael Kenn; Wolfgang Schreiner; Daniela Weinmann; Mario Rothbauer; Reinhard Windhager; Hans‑Joachim Gabius; Stefan Toegel (Histochemistry and Cell Biology, 2022)
Galectin-4 (Gal-4) is a member of the galectin family, which have been identified as galactose-binding proteins. Gal-4 possesses two tandem repeat carbohydrate recognition domains and acts as a cross-linking bridge in sulfatide-dependent glycoprotein routing. We herein document its upregulation in osteoarthritis (OA) in correlation with the extent of cartilage degradation in vivo. Primary human OA chondrocytes in vitro respond to carbohydrate-inhibitable Gal-4 binding with the upregulation of pro-degradative/-inflammatory proteins such as interleukin-1β (IL-1β) and matrix metalloproteinase-13 (MMP-13), as documented by RT-qPCR-based mRNA profiling and transcriptome data processing. Activation of p65 by phosphorylation of Ser536 within the NF-κB pathway and the effect of three p65 inhibitors on Gal-4 activity support downstream involvement of such signaling. In 3D (pellet) cultures, Gal-4 presence causes morphological and biochemical signs of degradation. Taken together, our findings strongly support the concept of galectins acting as a network in OA pathogenesis and suggest that blocking their activity in disease progression may become clinically relevant in the future.

A performance-based tabular approach for joint systematic improvement of risk control and resilience applied to telecommunication grid, gas network, and ultrasound localization system - Ivo Häring; Mirjam Fehling-Kaschek; Natalie Miller; Katja Faist; Sebastian Ganter; Kushal Srivastava; Aishvarya Kumar Jain; Georg Fischer; Kai Fischer; Jörg Finger; Alexander Stolz; Tobias Leismann; et al. (Environment Systems and Decisions, 2021)
Organizational and technical approaches have proven successful in increasing the performance and preventing risks at socio-technical systems at all scales. Nevertheless, damaging events are often unavoidable due to a wide and dynamic threat landscape and enabled by the increasing complexity of modern systems. For overall performance and risk control at the system level, resilience can be a versatile option, in particular for reducing resources needed for system development, maintenance, reuse, or disposal. This paper presents a framework for a resilience assessment and management process that builds on existing risk management practice before, during, and after potential and real events. It leverages tabular and matrix correlation methods similar as standardized in the field of risk analysis to fulfill the step-wise resilience assessment and management for critical functions of complex systems. We present data needs for the method implementation and output generation, in particular regarding the assessment of threats and the effects of counter measures. Also included is a discussion of how the results contribute to the advancement of functional risk control and resilience enhancement at system level as well as related practical implications for its efficient implementation. The approach is applied in the domains telecommunication, gas networks, and indoor localization systems. Results and implications are further discussed.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Intraclonal competitive fitness of longitudinal cystic fibrosis Pseudomonas aeruginosa airway isolates in liquid cultures - Nina Cramer; Sebastian Fischer; Silke Hedtfeld; Marie Dorda; Burkhard Tümmler (Environmental Microbiology, 2020)
Summary The metabolically versatile Pseudomonas aeruginosa inhabits biotic and abiotic environments including the niche of cystic fibrosis (CF) airways. This study investigated how the adaptation to CF lungs affects the within‐clone fitness of P. aeruginosa to grow and persist in liquid cultures in the presence of the clonal ancestors. Longitudinal clonal P. aeruginosa isolates that had been collected from 12 CF donors since the onset of colonization for up to 30 years was subjected to within‐clone competition experiments. The relative quantities of individual strains were determined by marker‐free amplicon sequencing of multiplex PCR products of strain‐specific nucleotide sequence variants, a novel method that is generally applicable to studies in evolutionary genetics and microbial ecology with real‐world strain collections. For 10 of the 12 examined patient courses, P. aeruginosa isolates of the first years of colonization grew faster in the presence of their clonal progeny than alone. Single growth of individual strains showed no temporal trend with colonization time, but in co‐culture, the early isolates out‐competed their clonal progeny. Irrespective of the genetic make‐up of the clone and its genomic microevolution in CF lungs, the early isolates expressed fitness traits to win the within‐clone competition that were absent in their progeny.

Edaphosauridae (Synapsida, Eupelycosauria) from Europe and their relationship to North American representatives - Frederik Spindler; Sebastian Voigt; Jan Fischer (PalZ, 2020)

Bone allografts combined with adipose-derived stem cells in an optimized cell/volume ratio showed enhanced osteogenesis and angiogenesis in a murine femur defect model - Johannes M. Wagner; Nicolas Conze; Guido Lewik; Christoph Wallner; Jan C. Brune; Stephanie Dittfeld; Henriette Jaurich; Mustafa Becerikli; Mehran Dadras; Kamran Harati; Sebastian Fischer; Marcus Lehnhardt; et al. (Journal of Molecular Medicine, 2019)

Specialisation and diversity of multiple trophic groups are promoted by different forest features - Caterina Penone; Eric Allan; Santiago Soliveres; María R Felipe‐Lucia; Martin M Gossner; Sebastian Seibold; Nadja K. Simons; Peter Schall; Fons van der Plas; Peter Manning; Rubén D. Manzanedo; Steffen Boch; et al. (Ecology Letters, 2019)
While forest management strongly influences biodiversity, it remains unclear how the structural and compositional changes caused by management affect different community dimensions (e.g. richness, specialisation, abundance or completeness) and how this differs between taxa. We assessed the effects of nine forest features (representing stand structure, heterogeneity and tree composition) on thirteen above‐ and belowground trophic groups of plants, animals, fungi and bacteria in 150 temperate forest plots differing in their management type. Canopy cover decreased light resources, which increased community specialisation but reduced overall diversity and abundance. Features increasing resource types and diversifying microhabitats (admixing of oaks and conifers) were important and mostly affected richness. Belowground groups responded differently to those aboveground and had weaker responses to most forest features. Our results show that we need to consider forest features rather than broad management types and highlight the importance of considering several groups and community dimensions to better inform conservation.

Entwicklung von Transportalternativen im Kalksteinbruch der Baumit GmbH - Manuel Mitterhauser; Sebastian Fischer; Herwig Seidl (BHM Berg- und Hüttenmännische Monatshefte, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Comprehensive analysis of the in vitro and ex ovo hemocompatibility of surface engineered iron oxide nanoparticles for biomedical applications - Florian Schlenk; Sebastian Werner; Martin Rabel; Franziska Jacobs; Christian Bergemann; Joachim H. Clement; Dagmar Fischer (Archives of Toxicology, 2017)

Erratum zu: CO2 storage related groundwater impacts and protection - Sebastian Fischer; Stefan Knopf; Franz May; Dorothee Rebscher (Grundwasser, 2016)

CO2 Storage related Groundwater Impacts and Protection - Sebastian Fischer; Stefan Knopf; Franz May; Dorothee Rebscher (Grundwasser, 2016)

Effects of fen management and habitat parameters on staphylinid beetle (Coleoptera: Staphylinidae) assemblages in north-eastern Germany - Hannes Hoffmann; Peter Michalik; Sebastian Görn; Klaus Fischer (Journal of Insect Conservation, 2016)

Report on the 43rd Annual Meeting of the DPG-Working Group Nematology - Matthias Daub; Ulrike Hakl; Leendert PG Molendijk; Corrie Schomaker; Thomas H Been; Thea G van Beers; Sevda Jivishova; Emil Jivishov; Michael Keusgen; Roman Bluemel; Daniel Fischer; Florian MW Grundler; et al. (Journal of Plant Diseases and Protection, 2015)

Effects of fen management on bird communities in north-eastern Germany - Sebastian Görn; Frank Schulze; Klaus Fischer (Journal of Ornithology, 2015)

Interclonal gradient of virulence in the P seudomonas aeruginosa pangenome from disease and environment - Rolf Hilker; Antje Munder; Jens Klockgether; Patricia Moran Losada; Philippe Chouvarine; Nina Cramer; Colin F. Davenport; Sarah Dethlefsen; Sebastian Fischer; Huiming Peng; Torben Schönfelder; Oliver Türk; et al. (Environmental Microbiology, 2015)
Summary The population genomics of P seudomonas aeruginosa was analysed by genome sequencing of representative strains of the 15 most frequent clonal complexes in the P . aeruginosa population and of the five most common clones from the environment of which so far no isolate from a human infection has been detected. Gene annotation identified 5892–7187 open reading frame ( ORFs ; median 6381 ORFs ) in the 20 6.4–7.4 M bp large genomes. The P . aeruginosa pangenome consists of a conserved core of at least 4000 genes, a combinatorial accessory genome of a further 10 000 genes and 30 000 or more rare genes that are present in only a few strains or clonal complexes. Whole genome comparisons of single nucleotide polymorphism synteny indicated unrestricted gene flow between clonal complexes by recombination. Using standardized acute lettuce, G alleria mellonella and murine airway infection models the full spectrum of possible host responses to P . aeruginosa was observed with the 20 strains ranging from unimpaired health following infection to 100% lethality. Genome comparisons indicate that the differential genetic repertoire of clones maintains a habitat‐independent gradient of virulence in the P . aeruginosa population.

The Role of the BDNF Val66Met Polymorphism in Individual Differences in Long-Term Memory Capacity - Christian Montag; Andrea Felten; Sebastian Markett; Luise Fischer; Katja Winkel; Andrew Cooper; Martin Reuter (Journal of Molecular Neuroscience, 2014)

Assessing human impact on fen biodiversity: effects of different management regimes on butterfly, grasshopper, and carabid beetle assemblages - Sebastian Görn; Bernd Dobner; Axinia Suchanek; Klaus Fischer (Biodiversity and Conservation, 2014)

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Die Interkalibrierung nach EG-Wasserrahmenrichtlinie — Ergebnisse der ersten Interkalibrierungsphase 2005 bis 2007 - Sebastian Birk; Eva Bellack; Jürgen Böhmer; Katja Bunzel; Folker Fischer; Andreas Kolbinger; Ute Mischke; Jochen Schaumburg; Cornelia Schütz (WASSERWIRTSCHAFT, 2009)

Feather-like development of Triassic diapsid skin appendages - Sebastian Voigt; Michael Buchwitz; Jan Fischer; Daniel Krause; Robert Georgi (The Science of Nature, 2009)

Structure and markers of appropriateness, quality and performance of drug treatment over a 1-year period after hospital discharge in a cohort of elderly patients with cardiovascular diseases from Germany - Sebastian Harder; Philipp Fischer; Markus Krause-Schfer; Klaus Ostermann; Gottfried Helms; Helge Prinz; Mike Hahmann; Horst Baas (European Journal of Clinical Pharmacology, 2005)